Анализ влияния повышения тепловой мощности энергоблока АЭС на протекание запроектной аварии - Никуленков, Анатолий Геннадьевич; Черноусенко, Ольга Юрьевна; Никуленкова, Татьяна Владимировна (НТУ "ХПИ", 2018)
Учитывая потенциальную возможность для энергоблоков АЭС Украины увеличения тепловой мощности реакторной установки до 104 % от проектного значения, которая реализована в ряде стран, с одной стороны и уроки, извлеченные из аварии на АЭС Фукусима-1 с другой, возникает необходимость в анализе влияние повышения тепловой мощности энергоблока АЭС на протекание тяжелой запроектной аварии. В данной статье представлены результаты оценки времени достижения открытия импульсно-предохранительных клапанов компенсатора давления и максимального проектного предела по топливу (температура оболочки 1200 °С) для различных уровней мощности (до 104 % от проектного значения) при полном обесточивании энергоблока с отказом на запуск резервных дизель-генераторов. Обозначены основные допущения и подходы к моделированию тяжелой запроектной аварии при использовании расчетного интегрального одномерного кода RELAP5. Представлен сравнительный анализ протекания запроектной аварии реакторной установки на разных уровнях мощности.

Taking into consideration a potential opportunity for Ukrainian energy-generating units at the nuclear power plant to increase their thermal power up to 104 % of the design value that is available for many countries on the one hand and the lessons given by the accident at the nuclear power plant Fukushima-1 on the other hand we realize the need for the analyzing of the influence that an increase in the heat power of energy-generating unit at the NPP has on the behavior of grave beyond the design basis accident. This scientific paper gives the estimation data of the time required for the opening of pulse-safety valves of the pressure compensator and a maximum design safety limit for the fuel (the shell temperature of 1200 °C) for different power levels (up to 104 % of the design value) at a total de-energizing of the energy generating units in the case of the start-up failure of stand-by diesel generators. The main assumptions and approaches to the simulation of the grave beyond the design basis accident were defined using the design integral one-dimensional code RELAP5. A comparative analysis of the behavior of beyond the design basis accident of the reactor plant at different power levels has been given.
Analyzing the influence of an increase in the thermal power of energy generating unit at the nuclear power plant on the behavior of beyond the design basis accident
Keywords: атомная электростанция; паровая турбина; обесточивание; квазистационарный расчет; граничные условия; расчетная модель; steam turbine; de-energizing; quasistationary computation